Two-in-one: combined targeted chemo and gene therapy for tumor suppression and prevention of metastases. (February 2012) - Zhang, Min; Garbuzenko, Olga B; Reuhl, Kenneth R; Rodriguez-Rodriguez, Lorna; Minko, Tamara
Aims: To develop an approach for the effective treatment of ovarian tumor, prevention of metastases and limitation of side effects.Materials & Methods: In order to combine chemotherapy with genotherapy, we constructed a nanoscale-based tumor-targeted system containing two anticancer drugs, two antisense oligonucleotides (suppressors of cellular resistance) and a ligand specific to receptors overexpressed in cancer cells. The system was tested in a mouse metastatic xenograft model using tumor isolates from patients with ovarian carcinoma.Results: Treatment with the proposed nanosystem decreased primary tumor, prevented intraperitoneal metastases and limited adverse side effects.Conclusions: The advantages of the proposed targeted complex treatment of primary aggressive ovarian tumor and prevention of metastases make the proposed approach promising for clinical applications.